2003
DOI: 10.1021/ja036380g
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Cleavage of Aromatic Disulfide Radical Anions

Abstract: The electron transfer (ET) to a series of para-substituted diaryl disulfides, having the general formula (X-C(6)H(4)S-)(2), has been studied. The X groups were selected as to have a comprehensive variation of the substituent effect, being X = NH(2), MeO, H, F, Cl, CO(2)Et, CN, and NO(2). The reduction was carried out experimentally, using N,N-dimethylformamide as the solvent, and by molecular orbital (MO) ab initio calculations. The ET was studied heterogeneously, by voltammetric reduction and convolution anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
119
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(136 citation statements)
references
References 35 publications
(58 reference statements)
16
119
0
1
Order By: Relevance
“…This situation reflects, at least partially, the difficulties inherent to an adequate description of the intimate internal reorganization of the system required to finally produce the SÀS bond fission. Some interesting theoretical attempts to clarify this question have been performed, such as the quantum chemical model study reported by Uggerud, [16] in which four possible mechanisms for ECD of the disulfide bonds were investigated at different levels of theory, or the analysis of the electron transfer (ET) within the series of parasubstituted diaryl disulfides carried out by Antonello et al, [17] which showed that this process entails the formation of a loose radical anion with a singly occupied molecular orbital (SOMO) localized onto the SÀS bond. Despite these efforts, the actual situation is that the description of the SÀS bond cleavage is still a theoretical challenge even in the simplest disulfide system exhibiting a disulfide bond, S 2 H 2 , and the measured experimental value could only be reproduced when high-level G2 and complete basis set (CBS) methods were used.…”
Section: Introductionmentioning
confidence: 99%
“…This situation reflects, at least partially, the difficulties inherent to an adequate description of the intimate internal reorganization of the system required to finally produce the SÀS bond fission. Some interesting theoretical attempts to clarify this question have been performed, such as the quantum chemical model study reported by Uggerud, [16] in which four possible mechanisms for ECD of the disulfide bonds were investigated at different levels of theory, or the analysis of the electron transfer (ET) within the series of parasubstituted diaryl disulfides carried out by Antonello et al, [17] which showed that this process entails the formation of a loose radical anion with a singly occupied molecular orbital (SOMO) localized onto the SÀS bond. Despite these efforts, the actual situation is that the description of the SÀS bond cleavage is still a theoretical challenge even in the simplest disulfide system exhibiting a disulfide bond, S 2 H 2 , and the measured experimental value could only be reproduced when high-level G2 and complete basis set (CBS) methods were used.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of my knowledge this species has never before been described, although it shares close similarities with organic disulfide radical anions that have been studied in molecular systems as well as in proteins as reactive intermediates in S À S bond cleavage reactions. [13][14][15][16][17] These radical species contain a three-electron s bond, which derives from population of the SÀS s bonding orbital by two electrons and population of the s* orbital by one electron.…”
mentioning
confidence: 99%
“…5). A value close to or higher than 0.5 is expected in the case of a stepwise mechanism, while for a concerted Et mechanism a value much lower than 0.5 is expected (18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 92%